2021
DOI: 10.3390/ijms221910845
|View full text |Cite
|
Sign up to set email alerts
|

Adipokines as Immune Cell Modulators in Multiple Sclerosis

Abstract: Multiple sclerosis (MS), a chronic inflammatory and demyelinating disease of the central nervous system (CNS), is a major clinical and societal problem, which has a tremendous impact on the life of patients and their proxies. Current immunomodulatory and anti-inflammatory therapies prove to be relatively effective; however, they fail to concomitantly stop ongoing neurological deterioration and do not reverse acquired disability. The proportion to which genetic and environmental factors contribute to the etiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 171 publications
0
19
0
Order By: Relevance
“…This condition leads to a pro-inflammatory status increasing levels of interleukin 6 (IL-6), TNF-alpha, and leptin, factors that are associated with MS pathogenesis [ 41 ]. Additionally, recent studies suggest that increased BMI and obesity play a major role in MS development and progression [ 42 ]. Obesity and MS can lead to altered adipokine release into the blood circulation.…”
Section: Comorbidities In Ms As An Independent Factor Of Pathology—th...mentioning
confidence: 99%
See 3 more Smart Citations
“…This condition leads to a pro-inflammatory status increasing levels of interleukin 6 (IL-6), TNF-alpha, and leptin, factors that are associated with MS pathogenesis [ 41 ]. Additionally, recent studies suggest that increased BMI and obesity play a major role in MS development and progression [ 42 ]. Obesity and MS can lead to altered adipokine release into the blood circulation.…”
Section: Comorbidities In Ms As An Independent Factor Of Pathology—th...mentioning
confidence: 99%
“…This activates inflammatory pathways and increases the infiltration of immune cells in the CNS. Moreover, increased levels of pro-inflammatory cytokines in MS release pro-inflammatory adipokines and disrupt adipokine pathway, creating a feedback loop [ 42 ]. Pathophysiologically, obesity affects MS by promoting chronic inflammation, altering the endocrine system by disturbing the secretion of adipokines and influencing the gut microbiota [ 42 ].…”
Section: Comorbidities In Ms As An Independent Factor Of Pathology—th...mentioning
confidence: 99%
See 2 more Smart Citations
“…IL-6, IL-1β, TNF-α, IFN-γ, and CRP); disrupted adipokine production (e.g. leptin and adiponectin); and changes in the intestinal microbiome [10][11][12]. Furthermore, some authors have indicated that obesity may increase the risk of MS, leading to a decreased bioavailability of vitamin D, while in turn, a low concentration of vitamin D correlates with a pro-inflammatory state [13,14].…”
Section: Introductionmentioning
confidence: 99%